The Development of the Person in the Context of Human Talent Management - Aguirre Palma, Boris (2013)
The development of individuals in the context of talent management is related to their education and personal growth oriented future. The development of people is a set of organized learning experiences provided by the organization within a specified period to provide an opportunity to improve performance or human growth. lt involves three areas of activities: training, education and development. The Human Resources Management function works in organizational change and development in various methods of people development, in order to focus them to support the implementation of the strategies and objectives of their posts, on this basis, establishes the person as its most important intangible active and runs preeminence that proper performance and development depends on the success or failure of the company. The certainty that people are the most important to the company, born from its mission, vision and objectives, and concrete when the economy and profitability of organizations is unbeatable, says the staff and the work environment is appropriate. However, how far the axiom that people are the key intangible asset of enterprises and the correct guidance of this really depends on the success of the production and business profitability is applied? Let's get to the heart of this article, which has as its main purpose, to resolve these questions.